Mobile Monitoring—Open-Source Based Optical Sensor System for Service-Oriented Turbidity and Dissolved Organic Matter Monitoring - Schima, Robert; Krüger, Stephan; Bumberger, Jan; Paschen, Mathias; Dietrich, Peter; Goblirsch, Tobias (Frontiers in Earth Science, 2019)
The protection and sustainable use of aquatic resources require a better understanding of fresh water sources, limnic ecosystems, and oceans. The effects of global change, intensive use of natural resources and the complex interactions between humans and the environment show different effects at different scales. Current research approaches are not sufficient to appropriately take account of the heterogeneity and dynamics of aquatic ecosystems. A major challenge in applied environmental research is to extend methods for holistic monitoring and long-term observation technologies with enhanced resolution over both space and time. In this study, turbidity and the content of dissolved organic matter (DOM) are key parameters, as they are of importance for assessing the health of aquatic ecosystems and the state of ecosystem services (e.g., the provision of drinking water). Photonics and optical sensors as well as integrated circuits and open-source based components open interesting possibilities to overcome the current lack of adaptive and service-oriented sensor systems. An open source based optical sensor system was developed, which enables a user-specific, modular and adaptive in-situ monitoring of the turbidity and the dissolved organic substance content almost in real time. Quantification is based on attenuation or transmission measurements with two narrowband LEDs and corresponding detectors in the ultraviolet (DOM content) and infrared range (turbidity) of the electromagnetic spectrum. The developed in-situ sensor system shows a very high agreement with the results obtained using a laboratory photometer but with less methodological effort. First tests carried out in the area close to the city of Leipzig (Saxony, Germany) show promising results. The in-situ sensor system is able to acquire the optical attenuation with a sampling rate up to 0.1 Hz. Due to the fact that data is visualized directly with the help of web services, even the quality of data collection can be improved by assisting the selection of sampling points or a direct spatio-temporal data feedback. What this approach illustrates is the fact that open-source technologies and microelectronics can now be used to implement resilient and promising sensor systems that can set new standards in terms of performance and usability within applied environmental research.